Tinjauan Yuridis Terhadap Pengaturan Jabatan Notaris: Studi Komparasi Antara Indonesia dan Republik Rakyat Tiongkok (Lembaga Pengembangan Kinerja Dosen, 2025)
This research discusses a comparative analysis of the regulation concerning Notary Positions in Indonesia and The People’s Republic of China. Notary in Indonesia is regulated under Law No.2 of 2014 concerning amendments to Law No. 30 of 2004 concerning Notary Positions, however Republic of China has different regulations from Indonesia as provided in Notarization Law Of The People’s Republic Of China 2017. This research was conducted using doctrinal approach method supported by primary legal materials and secondary legal materials. Based on this research analysis, it can be concluded that there are several similarities including the authority to make Notarial deeds and to validate legal documents, affiliated with Notary Organization, and the Notary’s liability in administrative, civil and criminal aspects. However, there are several differences about Notarial regulations in Tiongkok that can be applied in Indonesia such as the qualifications required for being a Notary, and the collective system in Notarial office.